Assessment of rural satisfaction with local organizations services In ILAM province - Alireza darban astaneh (تحقیقات کاربردی علوم جغرافیایی)
Today in democratic governments, accountability to people and obtain the consent of them form local services is important for people's participation in local governance and consequently it is important to organizational success. In rural areas, wide range of services offered by local public organizations. Rural Satisfaction with the quality of their services, is one of the public performance indicators. The purpose of this study was to measure and analyze the rural people satisfaction from services quality of local organizations in Ilam province. Research Statistical Unit, is all villages with over 20 households in Ilam province. Research Statistical population is all members of the village councils and the study was done by counting all. The overall 1130 questionnaires were collected from 398 villages. The data were collected using a closed questionnaire.The model of Service Quality Gaps was used to assessment of villager’s satisfaction and One sample Chi-square used to analysis and assessment of comments. Also Cluster analysis was used to compare and cluster the villagers' satisfaction and one way ANOVA tests and Duncan's post hoc test was used to compare the satisfaction of villagers in different counties. The results showed that the villagers have little satisfaction in all of the local organizations. Cluster analysis results show that villagers are the most satisfaction from primary education, rural health centers and telephone services.  Also ANOVA results show that villagers in Dehloran County are less and Ilam County most satisfied with the public services. Correlation analysis revealed that a positive correlation exists between index of rural enjoyment and the public consensus. Also there is a negative correlation between distance of accessibility index and the public consensus.